Shallow-water carbonate facies herald the onset of the Palaeocene-Eocene Thermal Maximum (Hazara basin, Northern Pakistan) - Mubashir Ali; Giovanni Coletti; Luca Mariani; Andrea Benedetti; Muhammad-Jawad Munawar; Saif Ur Rehman; Pietro Sternai; Daniela Basso; Elisa Malinverno; Khurram Shahzad; Suleman Khan; Muhammad Awais; et al. (Journal of Asian Earth Sciences: X, 2024)
We investigate the Palaeocene succession of the Hazara Basin (Northern Pakistan) to better understand the impact of climate change on marine carbonate-producing organisms. These shallow-water carbonates, deposited during the Late Palaeocene, before the onset of the Palaeocene-Eocene Thermal Maximum, were studied using a quantitative approach to highlight changes in the skeletal assemblage. We recognise a decrease in the abundance of colonial corals and green calcareous algae and an increase in larger benthic foraminifera and red calcareous algae from the early Thanetian to the late Thanetian. Increasing temperatures may represent a plausible cause for the decline of the more sensitive colonial corals in favor of the more tolerant larger benthic foraminifera. A similar pattern is observed in most successions deposited along the margins of the Neotethys Ocean, suggesting a connection with the Late Palaeocene environmental changes that heralded the PETM hyperthermal event. Our stratigraphic analysis of the Hazara Basin strata suggests that the biotic turnovers occurred during the Palaeocene – Eocene transition started already before the onset of the Palaeocene Eocene Thermal Maximum as recorded by the geochemical proxies.